Gestión financiera del Gobierno Autónomo Descentralizado Parroquial de Ricaurte - Cercado Palma, Bayron Otton (2017)
The Autonomous Rural Parochial Government of Ricaurte is an Entity with public resources to the benefit of the community, counting on a percentage of the general budget of the State, with which it is in charge of encouraging the sustainable development of its territorial Parochial Rural to be able to guarantee the realization of good living through the implementation of Rural Parochial Public Policies within their constitutional and legal powers, according to the Law "COOTAD" chapter IV article 64, functions of the Decentralized Rural Parochial Autonomous Governments. In the following study I will determine the records and the treatment that the Autonomous Government of the Parish of Rural Ricaurte of Ricaurte carries with its income and expenses of its annual budget designated by the State in its different projects and works that are in charge of said Parish Board. I will try to verify with the corresponding laws that are due the Public Institutions to function correctly in their Financial Management, and all their general proceeding. Finally, the case study in the Autonomous Government of the Rural Parish of Ricaurte will be based on its Financial Management and the good management of each item as the law stipulates, guaranteeing correct information based on the laws of the Country.